2021
DOI: 10.3390/ijerph18094888
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Changes and Their Associations with Quality of Life during COVID-19 Lockdown: A Cross-Sectional Study in the French-Speaking Part of Switzerland

Abstract: The lockdown due to the COVID-19 pandemic has led to various sudden changes in a large number of individuals. In response, the question of how individuals from different social and economic strata cope with those changes has arisen, as well as how much they have affected their mental well-being. Choosing strategies that cope with both the pandemic and the well-being of the population has also been a challenge for different governments. While a large number of studies have investigated the mental health of peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Two studies from Hong Kong and Switzerland also found that people who were worried about getting COVID-19 had a lower HRQoL. 14,15 Similar to our findings, Duay et al 15 found no association between adherence to social distancing and HRQoL.…”
Section: Discussionsupporting
confidence: 87%
“…Two studies from Hong Kong and Switzerland also found that people who were worried about getting COVID-19 had a lower HRQoL. 14,15 Similar to our findings, Duay et al 15 found no association between adherence to social distancing and HRQoL.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, even if the cause of anxiety or stress was not fully rational, this does not mean that stress did not affect the course of treatment. Nonetheless, various stress-related phenomena emerged in entire populations during the pandemic and the general atmosphere likely affected our respondents as well [ 23 , 24 , 25 , 26 ]. Our patients are routinely advised to follow an active lifestyle, and this recommendation could be of great importance, especially in terms of their psychological well-being.…”
Section: Discussionmentioning
confidence: 99%